Comparison of Ivor-Lewis versus Sweet procedure for middle and lower thoracic esophageal squamous cell carcinoma: A STROBE compliant study. Issue 6 (February 2019) - Wang, Jun; Wei, Ning; Jiang, Nanqing; Lu, Yiming; Zhang, Xiaoying
Abstract : Abstract: Our study compared the Ivor-Lewis and Sweet procedures used for treating middle and lower thoracic esophageal squamous cell carcinoma and assessed the associated perioperative complications and long-term survival rates of the patients. This retrospective study involved 624 middle and lower thoracic esophageal squamous carcinoma patients who received either Ivor-Lewis (n = 325) or Sweet (n = 299) procedures at our hospital. Further, the perioperative conditions and long-term survival rates were analyzed for both groups. Relative to the Sweet group, the Ivor-Lewis group showed lower volume of drainage within 24 hours after operation (400 (300–500) ml vs 550 (400–658) ml, P  = .031). Although we found no significant differences in major postoperative complications between the groups (72 (22.2) vs 65 (21.7), P  = .90), there were significant differences observed in minor postoperative complications between the Ivor-Lewis and Sweet groups (59 (18.2) vs 32 (10.7), P  = .008). Perioperative death rates remained comparable for the 2 groups (2 (0.6) vs 2 (0.7), P  > .99). Further, comparison of the 2 groups revealed that the Ivor-Lewis group had increased number of dissected lymph nodes, (20 (4–42) vs 16 (3–31), P  < .001), especially in the upper mediastinum (4 (0–5) vs 2 (0–2), P  < .001). The long-term survival rates did not differ significantly between the 2 groups (Kaplan-Meier method, P  = .95; Cox regression, P  = .20). These findings suggest that perioperative complications and long-term survival rates were comparable for both patients groups. Patients receiving the Sweet procedure had reduced minor postoperative complications compared to those receiving the Ivor-Lewis procedure. Due to improved quality of lymph node dissection in the upper mediastinum, the Ivor-Lewis procedure may have advantages over the Sweet procedure for treating patients with esophageal cancer with enlarged lymph nodes in the upper mediastinum.